SURVEY PERILAKU MASYARAKAT TERHADAP POPULASI TUNGAU DEBU RUMAH DI SEKITAR RUMAH PENDUDUK KELURAHAN RANOTANA WERU KECAMATAN WANEA - Tjandra, Winner S. (eBiomedik, 2013)
Abstract: House Dust Mites are found in damp houses, mattresses, pillows, bolsters, carpets as well as the other variety of home furnishings. House Dust Mites can be a serious problem for human health. For people who are susceptible to house dust mites can trigger allergic reactions such as asthma, rhinitis, conjunctivitis and atopic dermatitis. The location of the research was held in Ranotana Village of Wanea District. In this location there are many home stay, that most of the residents has less attention to the hygiene of their rooms. Purpose of this thesis research is to find a picture of the behavior the society courses on house dust mites araound the house people in Ranotana Village of Wanea District. Advance research methodsin use is a descriptive study using a questionnaire survey method. Sample is determined by simple random sampling method. Number of sampe in this study as many as 95 house holder and were collected using a questionnaire containing a list of questions. Based on research done the people in Ranotana Village of Wanea District has the poor level of knowledge, in attitude most have good attitude, and have good in action. Keywords: Behavior, House Dust Mites, Population Abstrak: Tungau Debu Rumah banyak ditemukan pada rumah yang lembab, kasur, bantal, guling, karpet serta berbagai perabot rumah yang lain.TDR dapat menjadi masalah yang serius bagi kesehatan manusia. Bagi orang yang rentan TDR dapat menjadi pencetus timbulnya reaksi alergi seperti asma, rhinitis, konjungtivitis dan dermatitis atopik. Lokasi penelitian dilakukan di Kelurahan Ranotana Weru Kecamatan Wanea. Lokasi ini banyak terdapat rumah kost, dimana sebagian besar penghuni kost kurang memperhatikan kebersihan kamarnya. Tujuan penelitian ini adalah mencari gambaran perilaku masyarakat terhadap populasi tungau debu rumah di sekitar rumah penduduk Kelurahan Ranotana Weru Kecamatan Wanea. Metode penelitian yang digunakan adalah penelitian deskriptif dengan metode survey menggunakan kusioner, sampel dalam penelitian ini sebanyak 95 Kepala Keluarga dan dikumpulkan dengan menggunakan kusioner yang berisikan pertanyaan. Berdasarkan hasil penelitian yang dilakukan penduduk Kelurahan Ranotana Weru Kecamatan Wanea masih memiliki pengetahuan yang kurang baik, dalam hal sikap memiliki sikap yang baik, dan dalam hal tindakan memiliki tindakan yang baik. Kata Kunci : Perilaku, Tungau Debu Rumah, Populasi